Interjú Niederhauser Emillel - Rácz, Márk (Gerundium, 2012)
AN INTERVIEW WITH EMIL NIEDERHAUSER. he interview with the elderly professor by Political Scientist Márk Rácz took place on January 11, 2009, a short time before the former’s death, at a senior citizens’ home in Üröm. During the conversation the retired professor, who originally had come from Bratislava, talked about his studies in his home city, his settling in Hungary, his survival in an increasingly communistoriented scholarly atmosphere, his non-partisan existence, and about his teaching career in Debrecen, which started in the 1950s. He also talked about his cool relationship with the party cadres and with the instructors of Marxism, and about the fact that, as a commuting ”suitcase professor”, he was looked upon by some with a degree of suspicion. However, his relationship with his students and his history-teaching colleagues was favourable, an asset that endured beyond his return to Budapest.